PROBING ANOMALOUS HZZ COUPLINGS AT THE LHeC - Çakır, İlkay Türk; Çakır, Orhan; Şenol, Abdulkadir; Taşçı, A. T. (World Scientific Pub Co Pte Lt, 2013)
We examine the sensitivity to anomalous couplings of the Higgs boson to neutral gauge bosons in a model-independent way at the Large Hadron electron Collider (LHeC). We have obtained the constraints on anomalous couplings for HZZ vertex via the process e-p→e-HqX. We find the accessible limits on the CP-conserving coupling bZ as (-0.12,0.43) and (-0.10,0.33), while the limits on CP-violating coupling βZ as (-0.32,0.32) and (-0.24,0.24) at the electron beam energy Ee = 60 GeV and Ee = 140 GeV , respectively.
Keywords: Z boson; High Energy Physics - Phenomenology; High Energy Physics - Phenomenology (hep-ph); LHeC; FOS: Physical sciences; Anomalous; Higgs